1997
DOI: 10.1523/jneurosci.17-19-07433.1997
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Bulb Recovery after Early Sensory Deprivation

Abstract: Olfactory bulbs retain the ability to acquire new neurons throughout life. Unilateral olfactory deprivation during the first postnatal month in rats results in a dramatic reduction in the size of the experimental olfactory bulb. Part of this reduction is attributable to the death of neurons and glia. To examine the regenerative capacity of the juvenile olfactory bulb, we developed a technique for reversible olfactory deprivation. Reversible blockade from postnatal day 1 (P1) to P20 or P30 results in reduced bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 38 publications
10
92
2
Order By: Relevance
“…To regulate olfactory input reversibly, naris occlusion plugs (Cummings et al, 1997) were used. These plugs were made of polyethylene tubing (SP35, Natume), silk thread (4 -0, Akiyama), and a piece of Japanese female hair to be used as a pull string.…”
Section: Methodsmentioning
confidence: 99%
“…To regulate olfactory input reversibly, naris occlusion plugs (Cummings et al, 1997) were used. These plugs were made of polyethylene tubing (SP35, Natume), silk thread (4 -0, Akiyama), and a piece of Japanese female hair to be used as a pull string.…”
Section: Methodsmentioning
confidence: 99%
“…Olfactory input is a critical factor for the survival of new neurons in the OB. Several studies using anosmic mice, 80 olfactory deprivation, [81][82][83] and various odorants 84,85 revealed that olfactory input promotes the survival of newly arrived neurons in the OB. A recent study revealed that new granule cells are eliminated during the postprandial period, and this elimination is enhanced by olfactory deprivation.…”
Section: Neuronal Maturation and Turnover In The Olfactory Bulbmentioning
confidence: 99%
“…The nose plug was fabricated as described in Cummings et al (1997). The plugs were constructed out of polyethylene tubing (PE 50; Becton Dickinson, Parsippany, NJ), silk surgical suture thread (3-0), and human hair.…”
Section: Animalsmentioning
confidence: 99%